Novel supramolecular affinity materials based on (−)-isosteviol as molecular templates - Lohoelter, Christina; Brutschy, Malte; Lubczyk, Daniel; Waldvogel, Siegfried R. (Beilstein Journal of Organic Chemistry, 2013)
The readily available ex-chiral-pool building block (−)-isosteviol was combined with the C3-symmetric platforms hexahydroxytriphenylene and hexaaminotriptycene providing large and rigid molecular architectures. Because of the persistent cavities these scaffolds are very potent supramolecular affinity materials for head space analysis by quartz crystal microbalances. The scaffolds serve in particular as templates for tracing air-borne arenes at low concentration. The affinities of the synthesized materials towards different air-borne arenes were determined by 200 MHz quartz crystal microbalances.
Keywords: affinity materials; (−)-Isosteviol; supramolecular chemistry; triphenylene ketals; triptycenes; templates